Impact of Early Oral Feeding on Nasogastric Tube Reinsertion After Elective Colorectal Surgery: A Systematic Review and Meta-Analysis - Wang, Yan; Zhang, Yanji; Hu, Xing; Wu, Hui; Liang, Shan; Jin, Jing; Wu, Yunjun; Cen, Yao; Wei, Zairong; Wang, Dali (Frontiers in Surgery, 2022)
Abstract Background Colorectal cancer is a common malignant tumor appearing in the gastrointestinal tract. Surgical resection is recognized as the best means to improve patient survival. However, it is controversial whether early oral feeding (EOF) after elective colorectal resection demonstrates safety and efficacy in concerned clinical outcomes. Methods We searched PubMed, Embase, Cochrane Library and CNKI from inception to September 2021. Two authors independently screened the retrieved records and extracted data. EOF was defined as feeding within 24 hours after surgery, while traditional oral feeding (TOF) was defined as the feeding that started after the gastrointestinal flatus or ileus was resolved. The primary outcome was nasogastric tube insertion, and the secondary outcomes were the length of hospital stay and total complications. Categorical data were combined using odds ratio (OR), and continuous data were combined using mean difference (MD). Results We screened 10 studies from 34 records after full-text reading, with 1199 patients included in the analysis. The nasogastric tube reinsertion (OR 1.69; 95% CI 1.08 to 2.64, p=0.02) was more frequent in the EOF group, and older ages (>60 years) were associated with higher risk of nasogastric tube reinsertion (OR 2.05; 95% CI 1.05 to 3.99, p=0.04). Reduced length of hospital stay (MD –1.76; 95% CI -2.32 to -1.21; p<0.01) and the rate of total complications (OR 0.49; 95% CI 0.37 to 0.65, p<0.01) were observed in EOF compared with TOF. Conclusions EOF was safe and effective for patients undergoing elective colorectal surgery, but the higher rate of nasogastric tube reinsertion compared with TOF should be resolved.